2014
DOI: 10.1159/000355580
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Indicators of Dental Caries in Saliva: An in vivo Study

Abstract: This study evaluated the superoxide dismutase (SOD) activity, copper and zinc levels in saliva of caries-active and caries-free individuals. Eighty healthy adults were divided according to WHO criteria: caries-free (DMFT = 0) and caries-active (DMFT >10). Saliva collected was estimated for SOD activity as well as copper and zinc levels using the atomic nitro blue tetrazolium chloride reduction method and absorption spectrophotometry, respectively. The Student t test was applied. In conclusion, SOD activity as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 27 publications
3
32
3
1
Order By: Relevance
“…Several metals, possibly of dietary origin, are present in saliva as well [48,49], with fairly high concentrations of Fe and Zn. Although elevated salivary Zn and Cu levels have been observed in individuals with dental caries [50,51], this could more likely reflect host response via induction of antioxidant enzymes in which Zn and Cu are required. In this study we found little association of these minerals/metals with microbial diversity or abundances of individual bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Several metals, possibly of dietary origin, are present in saliva as well [48,49], with fairly high concentrations of Fe and Zn. Although elevated salivary Zn and Cu levels have been observed in individuals with dental caries [50,51], this could more likely reflect host response via induction of antioxidant enzymes in which Zn and Cu are required. In this study we found little association of these minerals/metals with microbial diversity or abundances of individual bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the typical proteomic pattern, the separation of proteins and their visualization using a stain is necessary. Gel electrophoresis is one of the important tools available to separate proteins based on their relative mobility on application of electric current depending on the molecular mass for evaluation [5][6][7][8][9][10].…”
Section: Estimation Of Mucin Levelsmentioning
confidence: 99%
“…Saliva protects oral tissues in many ways. A constant flow of saliva eliminates accumulations of microorganisms from the oral cavity but saliva also contains many innate or acquired (antibodies) defense mechanisms (1).…”
Section: Introductionmentioning
confidence: 99%
“…Innate human salivary defense proteins such as lysozyme, lactoferrin and peroxidase are known to exert a wide antimicrobial activity against a number of bacterial, viral and fungal pathogens in vitro (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation